2014
DOI: 10.15376/biores.9.3.5542-5556
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Characterization of Epoxy/Luffa Composites: Investigation on Chemical Treatment of Fibers on Mechanical and Acoustical Properties

Abstract: This study focuses on the development of epoxy/luffa composites and the investigation of their mechanical and acoustical properties. The fibers underwent an alkalization treatment, and its effects on the mechanical and sound absorption properties of the composites were measured utilizing a universal testing machine and two-microphone transfer function impedance tube methods. The effects of chemical modifications on the fibers were studied using a scanning electron microscope (SEM). The thermal analyses of comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Improvements in absorption coefficients at all frequencies, especially at low frequencies of approximately 80 to 2000 Hz, were observed as the thickness of the nonwoven materials was increased. Yang et al (2003) and Jayamani et al (2014) observed an interesting decrease and increase of sound absorption coefficient at a specific frequency for the rice straw (1000 Hz), while for the luffa the corresponding value was 3100 Hz. This kind of decrease and increase was due to the specific characteristics of natural fibers reflecting sound at the specific frequency, but absorbing sound in the middle and high frequency ranges (Yang et al 2003).…”
Section: Morphological Investigation Of Wpf Materialsmentioning
confidence: 93%
See 4 more Smart Citations
“…Improvements in absorption coefficients at all frequencies, especially at low frequencies of approximately 80 to 2000 Hz, were observed as the thickness of the nonwoven materials was increased. Yang et al (2003) and Jayamani et al (2014) observed an interesting decrease and increase of sound absorption coefficient at a specific frequency for the rice straw (1000 Hz), while for the luffa the corresponding value was 3100 Hz. This kind of decrease and increase was due to the specific characteristics of natural fibers reflecting sound at the specific frequency, but absorbing sound in the middle and high frequency ranges (Yang et al 2003).…”
Section: Morphological Investigation Of Wpf Materialsmentioning
confidence: 93%
“…At lower concentration, PVA covers the fibers, the pores between the fibers are maintained and the porosity of each constituent remains open. But at higher concentration, the PVA creates a thin layer around the particles and obstructs the intra-fiber pores (Gle et al 2011;Jayamani et al 2014). As a result, a decrease in the acoustic properties was observed when the PVA concentration was 1.5 wt.%.…”
Section: Acoustic Properties Of Wpf / Pva Coated Nonwoven Matsmentioning
confidence: 99%
See 3 more Smart Citations